2019
DOI: 10.1016/j.icarus.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter's auroral-related stratospheric heating and chemistry III: Abundances of C2H4, CH3C2H, C4H2 and C6H6 from Voyager-IRIS and Cassini-CIRS

Abstract: We present an analysis of Voyager-1-IRIS and Cassini-CIRS spectra of Jupiter's high latitudes acquired during the spacecrafts' respective flybys in November 1979 and January 2001. We performed a forward-model analysis in order to derive the abundances of ethylene (C 2 H 4 ), methylacetylene (CH 3 C 2 H), diacetylene (C 4 H 2 ) and benzene (C 6 H 6 ) in Jupiter's northern and southern auroral regions. We also compared these abundances to: 1) lower-latitude abundances predicted by the 'Model A' photochemical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 57 publications
0
41
2
Order By: Relevance
“…Most of the imaged CH 3 fragments appear with much lower TKER, however. Table 1 shows several potential sources of slow CH 3 radicals, including three-body dissociations (6), (12) and (14) and the production of an electronically excited CH 3 partner (channel (16)), the relative likelihoods of which are discussed below. .…”
Section: (B) Ion Imaging Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the imaged CH 3 fragments appear with much lower TKER, however. Table 1 shows several potential sources of slow CH 3 radicals, including three-body dissociations (6), (12) and (14) and the production of an electronically excited CH 3 partner (channel (16)), the relative likelihoods of which are discussed below. .…”
Section: (B) Ion Imaging Studiesmentioning
confidence: 99%
“…The distributions for each photolysis wavelength are offset vertically for display purposes and the dotted lines in plots (A) and (C) show the square root of P(TKER)normalised to the same maximum valuein order to accentuate the high TKER tails. The TKER max values associated with the two-body fragmentation channels (4), (5) and (8) as well as the most exoergic three body fragmentations yielding CH 2 and/or CH 3 fragments (channels (12) and (6)) are also indicated by vertical arrows in panels (A) and (C). TKER max values for other many-body fragmentation channels can be derived from Table 1 but, as noted in the text, given the assumed TOF to TKER conversion scheme it is likely that the products from such many-body fragmentations would appear at TKER values well below TKER max .…”
Section: (D) Active Photofragmentation Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that these species still vary locally more sharply as a function of latitude than the factor of two to three indicated by the low spatial resolution observations of Cavalié et al 2013; we note that these variations cannot be studied with 1D models, by definition. Sinclair et al (2018Sinclair et al ( , 2019 already demonstrated that the auroral regions of Jupiter harbor chemistry influencing the hydrocarbons that is not seen elsewhere on the planet. The same may be also be true for H 2 O, but diskresolved observations with more resolution than with Herschel (2009-2010) would be required to test this hypothesis, possibly with the James Webb Space Telescope Norwood et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…They found that C 2 H 2 and C 2 H 4 were significantly enhanced at millibar and submillibar pressures under the aurora, while C 2 H 6 remained fairly constant. In addition, Sinclair et al (2019) found that heavier hydrocarbons like C 6 H 6 were also enhanced under the aurorae. This points to a richer chemistry than that seen at lower latitudes, increasing the production of several hydrocarbons and ultimately producing Jupiter's aerosols (Zhang et al 2013(Zhang et al , 2016Giles et al 2019).…”
Section: Discussionmentioning
confidence: 98%